Efektivitas Bantuan Pembangunan Peace Corps Amerika Serikat Di Indonesia - Listia Khairunnisa (Andalas Journal of International Studies (AJIS), 2017)
The focus of this research is to explain the U.S. Peace Corps’ aid effectiveness in assisting Indonesia from year 2010 to 2017. This research utilizes the five principles and twelve indicators of Paris Declaration as tools to explain the aid effectiveness. The method of this research is descriptive-analytical and uses interviews and observation as primary resources, also using books and articles as secondary resources. The result of this research shows that principles of Paris Declaration on Aid Effectiveness in Peace Corps Indonesia is almost effective in Local Alignment Principle, Harmonization Principle, and Mutual Accountability Principle. In addition to Policy Ownership Principle, English learning is not yet considered as a priority. Moreover, there are some differences in development plan and real activities that makes it become unoperational strategy. In Managing for Result Principle, since 2010, the amount of students, teachers and communities whose interact with the volunteer of Peace Corps keep increasing but there is no official framework that shows development result oriented.  Keywords: Peace Corps, Peace Corps Indonesia, foreign aid, United States, Bappenas